2015
DOI: 10.1590/1982-43272560201509
|View full text |Cite
|
Sign up to set email alerts
|

Intervention in Autism: Social Engagement Implemented by Caregivers

Abstract: To become involved in states of social engagement with their caregivers is a core deficit of children with autism. This study verified the effectiveness of an intervention with caregivers for the promotion of social engagement in their children with autism. The interactions of seven dyads were video recorded before, during and after the intervention in order to record the duration of eleven states of the children’ attention engagement, coded as social engagement (SE) or non-social engagement (NSE). Eight hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
1
0
8
Order By: Relevance
“…This may present tension between parents and professionals on how to respond to children with ASD. Only two other Latin American studies related to ASD were found, both based in Brazil; one that focused on child characteristics of ASD and one that focused on a parent training program (Czermainski et al, 2014; Santos et al, 2015). Overall, there is limited research on ASD in Latin America.…”
mentioning
confidence: 99%
“…This may present tension between parents and professionals on how to respond to children with ASD. Only two other Latin American studies related to ASD were found, both based in Brazil; one that focused on child characteristics of ASD and one that focused on a parent training program (Czermainski et al, 2014; Santos et al, 2015). Overall, there is limited research on ASD in Latin America.…”
mentioning
confidence: 99%
“…Quanto ao delineamento dos estudos, observou-se que a maioria dos artigos incluídos tratam de ensaios clínicos 5,6,11,12,13,16,17,[20][21][22][23] , um refere-se a revisão do tipo sistemática 19 , um estudo transversal observacional 15 , dois estudos do tipo observacional descritivo. refira ao fato de este ser um país onde há maiores investimentos e recursos financeiros, quando comparados aos demais países que publicaram sobre o assunto, como o Brasil, por exemplo.…”
Section: Análise De Dadosunclassified
“…A orientação familiar é uma ferramenta importante e efetiva quando se conhece o contexto e a realidade social na qual as famílias estão inseridas 4 , que são informações cruciais para a avaliação e o tipo de abordagem que deverá ser tomado com as crianças e os familiares. Um programa de orientação familiar pode ser uma ferramenta útil para ajudar as famílias a lidar com o diagnóstico de TEA de seus filhos e promover uma melhora no desenvolvimento de linguagem e habilidades sociais, diminuindo o não engajamento social destas crianças 5 .…”
Section: Introductionunclassified
“…No entanto, embora haja evidências empíricas sobre os comportamentos que promovem a sustentação da interação cuidador-criança com TEA (Dos Santos et al, 2015), pouco se sabe sobre as características dos comportamentos do avaliador, em situação de hora lúdica diagnóstica, para além das publicações com enfoque psicodinâmico. É fundamental, portanto, conhecer os estilos interativos que tendem a predominar durante a hora lúdica pelo potencial que alguns comportamentos apresentam na promoção do engajamento infantil (Bosa et al, 2017).…”
unclassified